Ethiopia's Feed the Future (FtF) Supplemental Land Tenure Survey, 2019 - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
This dataset is a supplemental data to Feed the Future I (FtF) Ethiopia end-line Survey 2018. The purpose of the survey was to collect data on details of land access and use, women land rights, second-level land certification process, land related legal knowledge, and land rental market participation, which were not covered in FtF end-line Survey 2018. The survey covered a total of 1,984 rural households in four regions of Ethiopia that were interviewed during FtF end-line 2018. A structured household questionnaire was used to collect household, plot, and individual level data. Questionnaire modules related with land related legal knowledge and advice, and land rental market participation were administered separately for the head and spouse. Hence, a detail gender dis-aggregated data enables a closer analysis of gendered aspects of the impact of the second-level land certification program not only at household level (inter-household dimensions), but also within a household (intra-household aspects).